2013
DOI: 10.1016/j.geb.2012.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Legitimate punishment, feedback, and the enforcement of cooperation

Abstract: In dealing with peer punishment as a cooperation enforcement device, laboratory studies have typically concentrated on discretionary sanctioning, allowing players to castigate each other arbitrarily. While such 'vigilante justice' turns out to enhance cooperation when retaliation is prohibited, this comes at a substantial cost, as welfare levels are usually low. By contrast, in real life punishments are often meted out only insofar as punishers are entitled to punish and punishees deserve to be punished. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 62 publications
2
53
0
Order By: Relevance
“…In the next section, 20 Following [16], we find the following levels of antisocial punishment by treatment.…”
Section: Antisocial Punishmentmentioning
confidence: 90%
See 4 more Smart Citations
“…In the next section, 20 Following [16], we find the following levels of antisocial punishment by treatment.…”
Section: Antisocial Punishmentmentioning
confidence: 90%
“…Previous work has shown that there are a number of ways to increase the effectiveness of punishment by increasing the severity of punishment [8], coordinating punishment through a centralized mechanism [9][10][11][12], eliminating counter-punishment [13][14][15], eliminating antisocial punishment [16] or by allowing a longer timeline for learning how to use punishment [4]. In this paper, we propose using emotion regulation to increase the effectiveness of punishment.…”
Section: Related Experimentsmentioning
confidence: 99%
See 3 more Smart Citations